miR-132 serves as a diagnostic biomarker in gestational diabetes mellitus and its regulatory effect on trophoblast cell viability - Xuegui Zhou; Cuiping Xiang; Xiaoxia Zheng (BMC, 2019)
Abstract Background Gestational diabetes mellitus (GDM) leads to poor pregnancy outcomes. Strategies that improve trophoblast cell function are important methods for GDM treatment. This study aimed to investigate the expression and diagnostic potential of microRNA-132 (miR-132) in GDM patients, and further analyzed the effects of miR-132 on HTR-8/SVneo cell proliferation. Methods Quantitative real-time PCR was applied to estimate the expression of miR-132. A receiver operating characteristics curve (ROC) analysis was performed to evaluate the diagnostic value of serum miR-132 in GDM patients. In vitro regulation of miR-132 in trophoblast cell HTR-8/SVneo was achieved by cell transfection, and the effects of miR-132 on cell proliferation were assessed using CCK-8 assay. Results Expression of miR-132 was decreased in serum and placenta tissues in GDM patients compared with the healthy women. A negative correlation was found between the serum miR-132 levels and fasting blood glucose of the GDM patients. A ROC curve shown the serum miR-132 had considerable diagnostic accuracy with an area under the curve (AUC) of 0.898. High glucose (HG) treatment induced an inhibition in HTR-8/SVneo cell proliferation and the expression of miR-132. The overexpression of miR-132 in HTR-8/SVneo cells could markedly rescued the HG - induced suppressed cell proliferation. Conclusion All the data of this study revealed the reduced expression of miR-132 in serum and placenta tissues of GDM, and serum miR-132 serves a candidate biomarker in the diagnosis of GDM. miR-132 may act a protective role against GDM via enhancing the trophoblast cell proliferation.